2013
DOI: 10.1155/2013/787032
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Excess Weight Gain in Healthy Pregnant Women: Importance of Energy Intakes, Physical Activity, and Adherence to Gestational Weight Gain Guidelines

Abstract: Few studies have investigated if compliance with energy intakes, physical activity, and weight gain guidelines attenuate postpartum weight retention (PPWR) in mothers attending prenatal classes. We investigated whether (a) daily energy intakes within 300 kcal of estimated energy requirements (EERs), (b) walking more than 5000 steps/day, (c) targeting the recommended weight gain goals for prepregnancy BMI, and/or (d) achieving weekly or total gestational weight gain (GWG) recommendations minimized PPWR in 54 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
5
24
0
4
Order By: Relevance
“…Healthcare provider advice about GWG has influenced patient GWG goals [ 16 , 20 , 33 ] and total GWG [ 20 , 33 – 36 ], but more recent studies have not found any association between physician advice and GWG [ 9 , 14 ]. This may be the first study to find healthcare provider advice about GWG was not related to knowledge of GWG recommendations even though doctors were the most frequently reported source of health information during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare provider advice about GWG has influenced patient GWG goals [ 16 , 20 , 33 ] and total GWG [ 20 , 33 – 36 ], but more recent studies have not found any association between physician advice and GWG [ 9 , 14 ]. This may be the first study to find healthcare provider advice about GWG was not related to knowledge of GWG recommendations even though doctors were the most frequently reported source of health information during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Personal GWG goals have been associated with total GWG [ 14 , 15 ]. Moreover, when personal GWG goals are congruent with IOM GWG recommendations, adherence to IOM recommendations is more likely [ 16 , 17 ]. Studies have shown 30–79% of pregnant women know how much weight they should gain during pregnancy [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Con la implementación de la dieta personalizada durante tres meses acompañada de una orientación alimentaria previa, hubo un impacto positivo en los patrones de alimentación, en este estudio se encontró un incremento de 30.2% en la adecuación de energía recomendada de 90-110%, similar a lo reportado por Lee y colaboradores en Australia donde el porcentaje de mejora fue 28% (19). Al finalizar el estudio ninguna paciente sobrepasó los niveles de adecuación de energía, contrario a los reportes de Cohen y colaboradores en Canadá donde 54% de las mujeres con un plan de alimentación individualizado excedieron su ingesta diaria de calorías correspondiente (20).…”
Section: Discussionunclassified
“…Debido a que no hubo una adherencia del 100% al plan de alimentación otorgado, no se logró alcanzar el peso ideal en las pacientes de acuerdo a las semanas de gestación, sin embargo, se logró controlar este peso, reflejado en que no sobrepasó el peso real al peso proyectado. Un estudio en Canadá en mujeres con sobrepeso u obesidad con un plan de alimentación individualizado reportó un promedio de aumento de peso de 0.7 kg por semana (20), en comparación con 1.8 kg en promedio de ganancia de peso en nuestras pacientes en un mes.…”
Section: Discussionunclassified
“…In contrast to the minimal data available on women’s knowledge and perception of the effects that diet and exercise may have on pregnancy weight gain, there is documented evidence supporting the overall effects of energy intake and expenditure on weight gain and loss during pregnancy [17]. For example, Health Canada’s Healthy Weights Report states that healthy eating and physical activity (PA) practices are important for both weight management and general health [18], and other studies provide evidence to demonstrate that physical activity (PA) during pregnancy is beneficial for both mom and the baby [19,20].…”
Section: Introductionmentioning
confidence: 99%